2013
DOI: 10.4161/auto.23278
|View full text |Cite
|
Sign up to set email alerts
|

Ambra1knockdown in zebrafish leads to incomplete development due to severe defects in organogenesis

Abstract: These first authors contributed equally to this work. ‡ These senior authors contributed equally to this work.Keywords: Ambra1, zebrafish, autophagy, development, morpholino Abbreviations: AMBRA1, autophagy/Beclin 1 regulator 1; ATG, autophagy-related proteins; ATG5, autophagy-related 5; ATG7, autophagy-related 7; ATG14, autophagy-related 14; ATGMOs, translation blocking morpholinos; Baf A1, bafilomycin A 1 ;BCL2, B-cell CLL/lymphoma 2; BECN1, Beclin 1, autophagy-related; cDNA, complementary DNA; chd, chordin;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 41 publications
6
48
0
Order By: Relevance
“…Mice lacking Ambra1 are embryonic lethal at d E10-14 and show defective neural tube development and hyperproliferation of neural tissues. (In accord with this result, Benato and coworkers reported that knockdown of the zebrafish Ambra1 orthologs causes defects in body morphogenesis and brain development 20 ). rb1cc1 −/− mice are embryonic lethal at d E13.5-16.5, and display defects in heart and liver development.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Mice lacking Ambra1 are embryonic lethal at d E10-14 and show defective neural tube development and hyperproliferation of neural tissues. (In accord with this result, Benato and coworkers reported that knockdown of the zebrafish Ambra1 orthologs causes defects in body morphogenesis and brain development 20 ). rb1cc1 −/− mice are embryonic lethal at d E13.5-16.5, and display defects in heart and liver development.…”
Section: Introductionsupporting
confidence: 51%
“…The result is aberrant development of the cardiac chambers and the atrioventricular canal, as well as increased embryonic lethality. While previous studies have indicated that specific autophagy factors are required for development of the Drosophila eye, 12,43 the zebrafish brain, 19,20 and for mouse development (reviewed in ref. 7), our results provide the first evidence that autophagy contributes to the cardiac morphogenic program during vertebrate development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific set of primers was designed to amplify all the isoforms of ambra1a [37], ambra1b, beclin1 and lc3 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental findings have asserted that probiotic administration is beneficial to the i) IGF system and the gonadal development [26], ii) body growth [19,20,21,22,38,39], iii) immune system [18,40,41] and iv) reproduction [31,32,37]. …”
Section: Discussionmentioning
confidence: 99%